Learning styles in freshmen and senior university students from Buenos Aires - Freiberg Hoffmann, Agustín (2019)
Discusses differences in learning styles, according to socio-demographic and academic variables, and then examine its effect on the academic performance of learners. Participated 300 students from different faculties: Engineering, Medicine, and Psychology. Significant differences were observed in the Assimilator and Pragmatic styles according to age: the first in favor of older students, and the second of younger ones. The men stood out significantly in the Convergent and Adapter styles. Comparing freshmen and senior students, the first expressed a preference for the Pragmatic style, and the second for the Assimilator. The explanatory analysis indicated a negative influence of the Pragmatic style approach, and a positive for the Assimilator on academic performance.